Early warning system for coal mine safety production based on fuzzy-analytical hierarchy process - FANG Gang; DI Ming; LIU Han-yong; DANG Chun-cai; LAN Wei (Gong-kuang zidonghua, 2013)
In view of problem that early warning of coal mine safety production has many evaluation indexes which affected by many factors, an early warning system for coal mine safety production based on fuzzy-analytical hierarchy process was constructed. The system combines analytical hierarchy process with fuzzy comprehensive evaluation, uses analytical hierarchy process to determine the evaluation index weights, uses fuzzy evaluation matrix for fuzzy comprehensive evaluation, and finally uses the evaluation index weights and fuzzy comprehensive evaluation result to make synthesis of computing, so as to determine mine safety level and warning result. The practical application result demonstrates feasibility and effectiveness of the system.